Power of language and carriers meaning in communication discourse: كاظم مؤنس عزيز (Al-Academy, 2015)
It reveals speech communication whether it is legible audible or visible on a comprehensive formula inhabited open language on the modalities for reporting cases of the source say, making communication cognitive processes, is not to produce arguments as it is about the generation of the content of communication, so the contact of any kind remains practice for the cognitive action by the language in which it operates as a way agreed to their units between the poles of communication circle in the framework of a certain socio-cultural context, and that becomes the basis of the text of the message external referrals, making it feasible for multiple readings in semantic dimensions and deliberative